The Effect of Financial Conditions, Growth, and Debt to Equity Ratio on Company Sustainability with Corporate Governance as a Moderating Variable - Verawati Verawati (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
The purpose of this study is to get an empirical evidence whether financial condition, growth, and debt to equity ratio have a significant effect on company sustainability. Sample consists of companies that listed on Indonesian Stock Exchange since 2014 to 2017 and participating in the CGPI survey conducted by Indonesian Institute for Corporate Governance. Using multiple regression and moderated regression, the empirical results show that financial condition and debt to equity ratio has a significant positive effect on company sustainability, meanwhile growth does not have a significant effect in company sustainability. This study also try to get an empirical evidence whether corporate governance has a moderating effect to the relationship between financial condition and company sustainability, debt to equity ratio and company sustainability, growth and company sustainability. The result show that corporate governance does not have a moderating effect to the relationship between financial condition and company sustainability, debt to equity ratio and company sustainability, growth and company sustainability. Further study can use ASEAN CG Scorecard to obtain corporate governance scores and make a comparisons between industries.